Pelagomanes Trubovitz, Renaudie, Lazarus & Noble, 2022, n. comb. - Trubovitz, Sarah; Renaudie, Johan; Lazarus, David; Noble, Paula (Paleoceanography, 2022)
Pelagomanes ? piperata (Renaudie and Lazarus, 2015) n. comb. Plate 42, Figs. 6–8. Botryopera piperata n. sp., Renaudie and Lazarus, 2015, pl. 7, figs. 6–9B. Remarks. This species was not observed in the EEP, but it is the authors’ opinion that it fits the definition of Pelagomanes better than Botryopera , and thus is tentatively included here. The specimens on Pl. 42, Figs. 6–8 are from the Early Miocene Southern Ocean; photographs are reproduced from Renaudie and Lazarus (2015). Pelagomanes ? piperata has a distinct upward-curving hooklike apical horn, a strong triangular ventral horn, shoulders, ribs, and teeth on the thorax, which are all typical of Pelagomanes . In addition, this species has the unusual character of a plate covering the aperture of the thorax. A similar feature was present on some specimens of Pelagomanes ibburi n. sp. (Pl. 41, Figs. 1A – 6B), as well as one specimen of Pelagomanes? sp. B (Pl. 42, Fig. 2) and all specimens of Pelagomanes? sp. C (Pl. 42, Figs. 4A – 5B). Range. Late Oligocene—Pleistocene in the SO (reported by Renaudie and Lazarus, 2015). Published as part of Trubovitz, Sarah, Renaudie, Johan, Lazarus, David & Noble, Paula, 2022, Late Neogene Lophophaenidae (Nassellaria, Radiolaria) from the eastern equatorial Pacific, pp. 1-158 in Zootaxa 5160 (1) on page 82, DOI:10.11646/zootaxa.5160.1.1, http://zenodo.org/record/10544058